Durability assessment of asphalt mixtures for waterproofing and pavement of bridges - Michał Sarnowski; Piotr Radziszewski; Jerzy Piłat; Karol Kowalski; Jan Król (Budownictwo i Architektura, 2014)
Durability of bridge pavement is affected by two main factors: traffic conditions and environmental factors. In Central-European climate, in addition to traffic, a bridge pavement is loaded by low temperature and deicing agents. The bridge pavement can be constructed with either cement concrete or asphalt mixture technology. In Europe (including Poland) asphalt pavements are typically placed, composed with a surface and protection layer. Pavement is placed on the waterproofing layer after initial surface priming. Both protection and surface asphalt mixtures layers can lose their properties due to aging process or due to the water action. In this paper, the results of functional properties of asphalt mixtures testing used for protection and surface layers of bridge decks are presented. Tested mixtures were subjected to short term oven aging (STOA), long term oven aging (LTOA) and aging in high technological temperatures.